Characteristics, management and factors associated with poor outcomes in COVID-19 patients in Burkina Faso: insights from a 2021 large-scale ambispective study - Mamguem Kamga, Ariane; Ouédraogo, Samiratou; Kaboré, Firmin Nongodo; Traoré, Isidore Tiandiogo; Ouédraogo, Esperance; Poda, Armel; Diendéré, Arnaud Eric; Kania, Dramane; Badolo, Hermann; Sanou, Guillaume; Koné, Amariane; Kagoné, Therese Samdapawindé; et al. (Frontiers in Public Health, 2025)
ObjectivesTo assess treatment and identify predictive factors of worsening in COVID-19 patients.MethodsThis study was ambispective (both prospective and retrospective) and part of a multidisciplinary, multicenter project designed to generate epidemiological, sociological and anthropological data about the COVID-19 epidemic in Burkina Faso. Medical records of patients admitted for COVID-19 at the hospitals of Ouagadougou and Bobo-Dioulasso from March 2020 to April 2021 were reviewed. To identify predictive factors of severe complications, we used Poisson regression models.ResultsIn total, 1,511 patients were included, of whom 70% were aged ≤50 years, 59% were men and 97% were living in an urban area. Of the 86% of patients treated, 92.9% of them received the combo Azithromycin-hydroxychloroquine. A total of 78 (5.2%) patients experienced complications during hospitalization, and 49 (3.3%) patients died. Multivariate analysis identified patient's age, residence and comorbidity as factors associated with poor outcomes.ConclusionsAlthough most people had symptoms, most of them recovered without sequelae, and few patients had severe forms of disease. Age was a strong predictor of worse outcomes in this population.